Self-efficacy in breastfeeding support: a research on Italian midwifery students: Running head: Student’s self-efficacy in breastfeeding support - Prepelita, Tania; Ricchi, Alba; Messina, Marisa Patrizia; Molinazzi, Maria Teresa; Cappadona, Rosaria; Fieschi, Laura; Nespoli, Antonella; Guana, Miriam; Cervi, Gina; Parma, Dila; Mauri, Paola Agnese; Artioli, Giovanna; et al. (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the study: Maternal breastmilk represents the best nourishment for the newborn baby during its first six months, as it offers several benefits for the health and well-being of babies and mothers. In order to promote, protect and support effectively mother and child during breastfeeding, it is essential for midwives to be properly educated and to acquire highly professionalizing skills. This study aimed to evaluate the level of self-efficacy of the students attending the Degree Course of Midwifery, regarding the support of mother and child in breastfeeding. Method: A questionnaire of 37 items (Blackmanet al, 2015) validated in Italian by Mazzeo Melchionda (2019), was sent on-line to students of ten different Midwifery Degree Courses to assess their level of self-efficacy regarding the management of breastfeeding. Statistical analysis was carried out using statistic software R3.4.3 (The Foundation for Statistical Computing). Results: 158 questionnaires were collected from ten Italian Midwifery Degree Courses. The areas in which students showed a high level of self-efficacy in managing breastfeeding include: the benefits of breastfeeding; the child’s tendency to take the breast within an hour from childbirth and the relevance of skin to skin contact and rooming-in. Low levels of self-efficacy concerned the comfortably breastfeeding in public places and avoiding giving formula to the baby in its first six weeks of life. Conclusions: Generally the students attending Midwifery Degree Courses show a high level of self-efficacy in assisting mothers during breastfeeding and they prove to have a good knowledge of the benefits of breastfeeding to improve the health of mothers and their children. (www.actabiomedica.it)